Activity of decitabine as maintenance therapy in core binding factor acute myeloid leukemia. Issue 5 (22nd February 2022) - Senapati, Jayastu; Shoukier, Mahran; Garcia‐Manero, Guillermo; Wang, Xuemei; Patel, Keyur; Kadia, Tapan; Ravandi, Farhad; Pemmaraju, Naveen; Ohanian, Maro; Daver, Naval; DiNardo, Courtney; Alvarado, Yesid; et al.
Abstract: Background: Posttherapy measurable residual disease (MRD) positivity in core binding factor acute myeloid leukemia (CBF‐AML) is associated with shorter relapse‐free survival (RFS). Elimination of MRD measured via quantitative reverse transcription polymerase chain reaction (qRTPCR) for disease specific transcripts can potentially lead to better outcomes in CBF‐AML. Methods: We prospectively monitored the MRD using qRTPCR and flow cytometry on bone marrow samples in patients with newly diagnosed CBF‐AML who received decitabine (DAC) maintenance therapy after fludarabine/cytarabine/G‐CSF (FLAG)‐based induction/consolidation regimen. Negative qRTPCR (CMR) was defined as fusion transcript <0.01%. Results: Thirty‐one patients with CBF‐AML including 14 with t(8;21) and 17 with inv(16) received parenteral DAC as maintenance therapy. Fifteen patients (48.3%) had completed FLAG‐based induction/consolidation but with positive MRD (0.35%, range = 0.01%–0.91%) (Group 1). Sixteen patients (51.7%) could not complete recommended consolidations with FLAG‐based regimen (due to older age or complications) and were switched to DAC maintenance (Group 2). In Group 2, eight patients (50%) had undetectable MRD (Group 2A) (all had qRTPCR ≤ 0.01%) and the other eight patients (50%) had residual fusion product by qRTPCR (0.1%, range = 0.02%–0.36%) (Group 2B) prior to starting DAC. Amongst the 23 patients who had a PCR ≥ 0.01% before maintenance therapy (Groups 1 and 2B), 12 patients (52%) attained a CMR as their best response (responders). The median pre‐DAC qRTPCR amongst responders were 0.03% compared to 0.14% in nonresponders ( p  = .002). The median estimated molecular RFS amongst responders were 93.9 months. At a median follow‐up of 59.3 months (13.2–106 months) from DAC initiation, 16 patients (51.6%) had to be initiated on a second line of therapy (40%, 25%, and 100% patients, respectively, in Groups1, 2A, and 2B). The median estimated time to new treatment between responders was 112.4 versus 5.8 months in nonresponders (hazard ratio = 0.16, 95% confidence interval = 0.04–0.54); however, there were no difference in overall survival between these groups ( p  = .37). Conclusion: DAC is an effective maintenance therapy for CBF‐AML patients with persistent fusion transcript at a low level after FLAG‐based regimen. Attainment of CMR with DAC maintenance can lead to long‐term remission in patients who have persistent MRD positive after FLAG‐based regimen or are unable to receive the full course of consolidation therapy.